Screening and peculiarity of the biological action of synthetic plant growth regulators - Tsygankova, V.A.; Blume, Y.B. (Биополимеры и клетка, 1997)
As a result of biological screening among synthetic compounds that have growth regulatory activities in culture tissues in vitro and in vivo in plants, 5 perspective substances were chosen as the substitutes of phytohormones. Thus, it was found that Ivin (N-oxide 2,6-dimethylpyridine) revealed predominant cytokinin activity in vitro and a cytokinin-gibberelin activity in vivo; Methyur (Na-derivative 6-methylthyouracyl) showed an expressive cytokinin-gibberellin activity in vivo; Triamelon (Iodide tris (2,2-trimethylammoniummethyl phosphate) revealed a cytokinin-anxin activity in vitro; preparation D-107 (l-acetyl-amino-1-acetylthyo-2-oxo-2-phenylethan) revealed an auxine-like effect and the preparation N 2622 (derivative tetrahydrothyophendioxide) showed an expressive auxin activity in vivo. The model of mediated action of plant growth regulators through phytohormones is proposed.